(untitled) (Historia, 2021)
This study examines foreign African migrant labour supply to the Messina copper mines. The dependence of the mining industry on foreign migrant labour helped the company in the short term to reduce labour costs through the exploitative wage structure which the mineworkers had no choice but to accept. However, on a long term basis, this arrangement became a problem to the twin oppressive forces of capitalism and segregation systems because foreign migrant mineworkers acquired mining skills and monopolised the majority of job categories available for African mineworkers at the Messina mines to the exclusion of local Africans. In elaborating on foreign African migrant labour for the Messina mines, reference is made to the recruitment drive launched by the Witwatersrand Native Labour Association to secure foreign labour for the Witwatersrand gold mines. This serves to provide a comparative context which highlights the distinctiveness of the Messina mines.